Premature death after self-harm: a multicentre cohort study. - Bergen, H; Hawton, K; Waters, K; Ness, J; Cooper, J; Steeg, S; Kapur, N (2012)
BACKGROUND: People who self-harm have an increased risk of premature death. The aim of this study was to investigate cause-specific premature death in individuals who self-harm, including associations with socioeconomic deprivation. METHODS: We undertook a cohort study of patients of all ages presenting to emergency departments in Oxford, Manchester, and Derby, UK, after self-poisoning or self-injury between Jan 1, 2000, and Dec 31, 2007. Postcodes of individuals' place of residence were linked to the Index of Multiple Deprivation 2007 in England. Mortality information was supplied by the Medical Research Information Service of the National Health Service. Patients were followed up to the end of 2009. We calculated age-standardised mortality ratios (SMRs) and years of life lost (YLL), and we tested for associations with socioeconomic deprivation. FINDINGS: 30 950 individuals presented with self-harm and were followed up for a median of 6·0 years (IQR 3·9-7·9). 1832 (6·1%) patients died before the end of follow-up. Death was more likely in patients than in the general population (SMR 3·6, 95% CI 3·5-3·8), and occurred more in males (4·1, 3·8-4·3) than females (3·2, 2·9-3·4). Deaths due to natural causes were 2-7·5 times more frequent than was expected. For individuals who died of any cause, mean YLL was 31·4 years (95% CI 30·5-32·2) for male patients and 30·7 years (29·5-31·9) for female patients. Mean YLL for natural-cause deaths was 25·9 years (25·7-26·0) for male patients and 25·5 years (25·2-25·8) for female patients, and for external-cause deaths was 40·2 years (40·0-40·3) and 40·0 years (39·7-40·5), respectively. Disease of the circulatory (13·1% in males; 13·0% in females) and digestive (11·7% in males; 17·8% in females) systems were major contributors to YLL from natural causes. All-cause mortality increased with each quartile of socioeconomic deprivation in male patients (χ(2) trend 39·6; p<0·0001), female patients (13·9; p=0·0002), and both sexes combined (55·4; p<0·0001). Socioeconomic deprivation was related to mortality in both sexes combined from natural causes (51·0; p<0·0001) but not from external causes (0·30; p=0·58). Alcohol problems were associated with death from digestive-system disease, drug misuse with mental and behavioural disorders, and physical health problems with circulatory-system disease. INTERPRETATION: Physical health and life expectancy are severely compromised in individuals who self-harm compared with the general population. In the management of self-harm, clinicians assessing patients' psychosocial problems should also consider their physical needs. FUNDING: Department of Health Policy Research Programme.